(3QNGeGJ BdGJ GdSGYGJs - (3KGHJ Hf bQI Hf RgQhf GdMQGfj GdUCHrj, CHh GdMSf,J (B288 (3g` s ((3GHh GSMb GdUGHi s)
(3ChdgG (B:s
(3cJGH CHj GdMSf KGHJ Hf bQI QVi Gddg Yfg ai BdGJ GdSGYGJ GdJi JSei GdQNGeGJ s
(3BNQgG (B:s
(3hGLYd eG Hbi LfHkG hGVQHg ai GKfJi YTQ hGbSe eG GLJeY Ydi eG cfJ MaXJ aeG NQL agh CUGHY GdXd s
(3fbdkG Yf fSNI GdeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B98 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B101s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B217 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeI (B- (3U (B174 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
Keywords: (3GdUfGYI hGdCWYeIs